Mobile parenting socio-literacy learning apps (M-PASL) - Awanis, Romli; Mazlina, Abdul Majid; Aziman, Abdullah; Fatinatul Nazurah, Zainuddin; Mohamad Mohsin, Ismail (Centre for Applied Learning and Multimedia, UNIMAS, 2019)
In 2017, the Malaysian National Family Planning and Population Board, celebrated the theme “Families, Education and Wellbeing” as a reminder of the role of education to unlock the full potential of children and their wellbeing. Therefore, the aim of this research is to develop a mobile parenting socio-literacy for the family organization which is based on the premise that if experiences from the user personality can be captured in some useful form, the tool will be able to propose the solution in having good interaction between parents and their children. Thus, the parenting guide is proposed to help parents to educate their children by knowing their personality types for both parties which are parent and child. The research is beneficial to society in promoting parenting skills that can enhance parenting literacies. Furthermore, this research is related to interactive learning and decision support system for establishing the relationship between parents and children. Hence, this research will implement the Case Based Reasoning (CBR) technique which is able to give a solution to improve the relationship between parents and child to polish, monitor and improve the strength of each individual specifically and for a family organization holistically.